The Role of Information Technology on Employee Performance in Universities at New Normal Life Order After Covid-19 Pandemic - Upik Sri Sulistyawati; Bahruni Bahruni (International Journal of Social Science and Business, 2021)
Social restrictions have become a serious problem with regard to employee performance. In order to maximize employee performance, it is necessary to use information technology in the new normal life. The purpose of this study was to determine the effect of the use of information technology (X) on employee performance (Y). The type of research used is explanatory research with a quantitative approach. The sample used in this study were 46 respondents. The data analysis used is descriptive analysis, inferential analysis, and multiple linear regression. The sampling technique used is a saturated sample. The results of this study can be concluded that the independent variables have a significant influence on employee performance simultaneously and partially. The use of IT because it has the largest beta coefficient and t count. From the results of multiple linear regression, it can be concluded that the independent variable has a significant influence on the dependent variable, employee performance, which is 64.7%. While the remaining 35.3% is another variable that can affect employee performance. Other variables that can affect employee performance include employee motivation and ability. Information Technology has had an influence on employee performance at universities in the new normal life order during the Covid-19 period.